2017
DOI: 10.1111/bjd.15744
|View full text |Cite
|
Sign up to set email alerts
|

Does personalized melanoma genomic risk information trigger conversations about skin cancer prevention and skin examination with family, friends and health professionals?

Abstract: Personalized melanoma genomic risk information can prompt risk-appropriate discussions about skin cancer prevention and skin examinations with family and health professionals. Sharing this information with others might increase its impact on melanoma prevention and skin examination behaviours, and this process could be used to encourage healthy behaviour change within families.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
27
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(29 citation statements)
references
References 31 publications
2
27
0
Order By: Relevance
“…The changes to prevention behaviours described by some participants in this study (including those at low and average risk) suggest that the education and counselling aspect of result disclosure may help to motivate behaviour change. In addition, in the parent trial, most participants’ (79%) risk results were sent (with permission) to their general practitioner, which may enhance its clinical utility …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The changes to prevention behaviours described by some participants in this study (including those at low and average risk) suggest that the education and counselling aspect of result disclosure may help to motivate behaviour change. In addition, in the parent trial, most participants’ (79%) risk results were sent (with permission) to their general practitioner, which may enhance its clinical utility …”
Section: Discussionmentioning
confidence: 99%
“…This was a substudy of a pilot randomized controlled trial (parent study) that examined the feasibility, acceptability and impact of delivering personalized genomic risk of melanoma information to the public . Details of recruitment have been described in detail previously . Briefly, participants were recruited to the parent study from a cancer research database, and were eligible if they were aged 18–69 years, had no personal history of melanoma, were residing in New South Wales (Australia) and spoke English.…”
Section: Methodsmentioning
confidence: 99%
“…Our qualitative reviewers are stringent and rightly so. We aim to publish only the best qualitative work in the BJD – and six papers (Table ) have been selected for the special section . The studies offer insights into some of the intriguing ‘why?’ and ‘how?’ questions in our field.…”
Section: Six Qualitative Papers: Key Methodological Attributesmentioning
confidence: 99%
“…Smit et al . 's mixed‐methods study among the general public of the effects of receiving personalized melanoma‐related genomic risk information showed that tailored information could prompt conversations about skin examination and sun protection with family and health professionals . The sequential combination of quantitative and qualitative techniques enabled the questionnaires firstly to investigate ‘what’ conversations were triggered, followed by qualitative interviews to examine ‘why’ (or ‘why not?’).…”
Section: Six Qualitative Papers: Key Methodological Attributesmentioning
confidence: 99%
See 1 more Smart Citation